Detection of Hepatitis B Virus DNA in Chronic HBV Carriers and Correlation with HBeAg - Akther, Shamima; Husain, Md Anwar; Hossain, HS Mubarak (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Background: Chronic infection with hepatitis B virus causes a spectrum of diseases ranging from asymptomatic infective state to cirrhosis and hepatocellular carcinoma. The detection and quantification of HBV DNA plays an important role in diagnosing HBV infection as well as monitoring therapeutic responses. Methods: The aim of this study was to detect and quantited HBV DNA by real time PCR and to find out correlation HBeAg with HBV DNA in chronic carriers: The present study carried out among 61 previously diagnosed chronic hepatitis B patients. Results: The mean age of study population was 29.20 years. Among the 61 cases, 13(21.3%) were HBeAg positive and 48(78.7%) were HBeAg negative. By real time PCR, DNA detected in 45(73.8%) patients and 16(26.2%) patients were undetected. Association of HBeAg and HBV DNA was observed in 13 HBeAg positive cases, where 12(92.3%) had detectable DNA and in 48 HBeAg negative patients, 33(68.8%) had detectable DNA while 15(31.2%) were undetected. The present study observed a higher viral load (105copies/ml) among HBeAg positive patients (84.6%) than HBeAg negative patients (12.5%). Conclusion: The present study observed that, there was positive correlation among HBeAg and HBV DNA in chronic HBV carriers. However, there was some discordance observed among HBeAg and HBV DNA. Therefore, in addition to HBeAg, HBV DNA should be assessed for appropriate evaluation of CHB carriers. Chatt Maa Shi Hosp Med Coll J; Vol.15 (2); Jul 2016; Page 33-36